Peningkatan Pola Hidup Sehat Bagi Siswa Sekolah Dasar Negeri Desa Mojotrisno Melalui Edukasi Cuci Tangan, Memilah Sampah Dan Penanaman Tanaman - Hartanti, Dyah Ayu Sri; Khoiriyah, Ersa Andra Erlanda; Anisa, Umi; Rahmawati, Dewi Saroh (Institut Teknologi dan Sains Mandala, 2023)
This community service activity (PKM) aims to determine healthy lifestyles and environmental balance activities as well as hygiene concerns for studentss. The approach method used is a survey by distributing questionnaires that have been made. This activity began with material socialization consisting of an explanation of the importance of clean and healthy living behavior and how to sort organic and inorganic waste. After students know and realize this, then interest arises, namely students are interested in washing hands before and after eating using soap according to previously known information. In this case, the school appreciates the implementation team who have provided assistance and counseling with the achievement of a healthy lifestyle for students of SDN Mojotrisno with proper hand washing and the achievement of environmental preservation by planting plants and sorting organic waste and anorg.